Die nordfriesischen Inseln im 8. Jahrhundert.: Grabungsergebnisse von Handelsplätzen auf der Insel Föhr, Kr. Nordfriesland. - Majchczack, Bente Sven; Wunderlich, Tina; Wilken, Dennis (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
During the recent years, the North Sea Harbour Project investigated Early Medieval settlement sites (7th – 11th century) on the North Frisian Island of Föhr (Germany). The extensive fieldwork combined geophysical and geoarchaeological surveys as well as archaeological excavations to uncover the harbour locations as well as the settlement sites. The paper presents results from the harbour and trading sites of Goting and Witsum. The sites are located in small inlets along the edge of the high pleistocene cores of the islands with access to the low marshlands, beaches or tidal creeks. The geoarchaeological surveys show a clear maritime impact and navigability of the waterways, providing natural harbours for the settlements. The nearby ring fortress Borgsumburg housed a military elite and provided security and control for the trading sites. The prospections and excavations revealed a distinctive settlement pattern dominated by pit houses with traces of craft activities such as glass and amber working and a large-scale textile production. Remains from smithing workshops prove the construction or repair of boats. Numerous finds of imported goods from the core Frisian area, the Frankish empire, and Scandinavia indicate a strong connection to the cross-regional trade routes along the North Sea coasts. Especially the analysis of glass objects shows that the North Frisian Islands were strongly embedded in the North Sea trade networks of the 8th and 9th centuries with connections towards the Rhineland as well as the important emporium of Ribe (South Denmark).